2010
DOI: 10.1016/j.desal.2010.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on evaporation, condensation and production of a new Tubular Solar Still

Abstract: This paper describes a comparison between our first model of a Tubular Solar Still (TSS) and a second one. The first model was designed by our research group using a vinyl chloride sheet as a transparent tubular cover. Since then, we have designed the second model that has improved the assembly, economy and maintenance over the first model. In the second model, a polythene film was adopted as the cover. As a result, the cover weight and cost of the second model were noticeably reduced and the durability was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Ahsan et al presented in [21][22][23] results of study on the tubular solar still, including description of the mathematical model which takes into account properties of air in the still.…”
Section: Introductionmentioning
confidence: 99%
“…Ahsan et al presented in [21][22][23] results of study on the tubular solar still, including description of the mathematical model which takes into account properties of air in the still.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of solar still in arid areas at small or large scale could help in desalinating necessary needs of water either by purifying seawater, groundwater or recycling of wastewater (Kabeel and Almagar, 2013). The ongoing efforts in this endeavor revealed that a solar still use evaporation and condensation process which in nature generate rainfall (Ahsan et al, 2010) and such device limited by the high capital cost required to be applied on a small scale. However, to optimize and enhance this configuration to be used widely with possible low cost, this may require further modeling processes to forecast optimal performance and identify critical parameters related to still performance to lower its costs.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the improvement in fresh water yield from the solar still was 45% more than that for conventional solar still on the climatic condition of Chennai. Augmentations of tubular solar still productivity were discussed by Ahsan et al [13][14][15][16][17][18]. Arunkumar et al [19] investigated a concentric tubular solar still using air and water as cooling medium over the glass cover.…”
Section: Introductionmentioning
confidence: 99%